2011
DOI: 10.3109/0886022x.2011.615968
|View full text |Cite
|
Sign up to set email alerts
|

Survival Advantage of Normal Weight in Peritoneal Dialysis Patients

Abstract: Introduction: A high body mass index (BMI) is a positive predictor of outcome in hemodialysis. But reports for peritoneal dialysis (PD) have been less numerous. The aim of the present investigation was to study the association between BMI and survival among PD patients and to discuss the main risk factors affecting survival. Materials and methods: A total of 159 patients who received PD from 1 January 2006 to 31 December 2010 at the Department of Nephrology in the Third Affiliated Hospital of Soochow Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…29 However, obesity is found to be a risk factor for mortality in small number of peritoneal dialysis patients. 30 We did not found any associations between BMI values or obesity (BMI ! 30 kg/m 2 ) and mortality.…”
Section: Parametermentioning
confidence: 69%
“…29 However, obesity is found to be a risk factor for mortality in small number of peritoneal dialysis patients. 30 We did not found any associations between BMI values or obesity (BMI ! 30 kg/m 2 ) and mortality.…”
Section: Parametermentioning
confidence: 69%
“…In contrast, the impact of BMI on survival in peritoneal dialysis (PD) patients is inconsistent. Some studies have suggested a similar protective effect of BMI (12-15), some have suggested a neutral effect (11,16), and some have indicated that survival is worse in obese patients (17,18).The relationship between BMI and mortality might be different in dialysis patients of different ethnicities. Wong et al (9) were the first to report a difference in the impact of BMI on survival in white and Asian HD patients within the United States.…”
mentioning
confidence: 99%
“…In contrast, the impact of BMI on survival in peritoneal dialysis (PD) patients is inconsistent. Some studies have suggested a similar protective effect of BMI (12)(13)(14)(15), some have suggested a neutral effect (11,16), and some have indicated that survival is worse in obese patients (17,18).…”
mentioning
confidence: 99%
“…The influence of race on the outcomes of obesity in PD was confirmed by similar studies conducted in Asia[38] and in Australia and New Zealand[39]. Other studies reported either adverse effects[40,41] or no effect[42,43] of obesity on the survival of PD patients.…”
Section: Discussionmentioning
confidence: 64%